Effect of hetero-structured nano-particulate coating on the oxygen surface exchange properties of La0.6Sr0.4Co0.2Fe0.8O3-δ. (1st March 2019) - Samreen, Ayesha; Saher, Saim; Ali, Shahid; Seema, Humaira; Qamar, Affaq
Abstract: In this study, dense La0.6 Sr0.4 Co0.2 Fe0.8 O3-δ (LSCF) electrodes decorated with the novel hetero-structured ceramic oxide mixture in four different ratios of Ce0.8 Gd0.2 O2-δ (GDC) and La2 Mo2 O9 (LMO). The time-dependent conductivity transients were acquire using electrical conductivity relaxation (ECR) technique at a chosen conditions of temperature in the range of 650–850 °C and instantaneous p O2 step change between 0.2 and 0.8. Fitting of time-dependent conductivity to the appropriate non-equilibrium solutions of Fick's diffusion equation has yielded the chemical diffusion coefficient, D chem, and oxygen surface exchange coefficient, k chem . As expected, the D chem of the coated samples remained invariant, whilst the k chem is found to vary with the change in GDC-LMO coating mixture ratio. Substantial increase of a factor of 10 in the surface exchange coefficient is noticed for the LSCF coated with a 1:0.75 mixing ratio as compared to bare sample at 850 °C. The enhancement in k chem is attributed to the optimal triple-phase boundary (TPB) regions which promotes oxygen surface exchange kinetics. Thus, coating of selective ratio of hetero-structured oxide in a form of nano-particulate layer over the LSCF surface is considered to be a promising candidate for solid oxide fuel cell (SOFC) cathode. Highlights: Nano-particulate coating of Ce0.8 Gd0.2 O2-δ - La2 Mo2 O9 (GDC-LMO) mixture on LSCF. Electrical conductivity relaxation measurements in the temperature range of 650–850 °C. Chemical diffusion coefficient remained invariant. Enhancement in surface exchange coefficient by a factor of 10 for the selective composition of GDC-LMO coating mixture. Nano-particulate layer over the LSCF surface is considered to be a promising candidate for SOFC cathode.